Effects of Environmental Factors on Crayfish Abundance in the Boundary Water Canoe Area Wilderness - Servey, Nathan; Dow, Brennan; Burant, Brittany; Loden, Mason (My University, 2013)
The objective of this study was to investigate how crayfish in the Boundary Water Canoe Area Wilderness (BWCA) responded to lake productivity and water depth.
Color poster with text, photographs, and graphs.
Keywords: Crayfish; Boundary Water Canoe Area; Lake productivity; Water depth; Posters